Inside brokers - LI, Frank Weikai (Institutional Knowledge at Singapore Management University, 2021)
We identify the broker each corporate insider trades through, and find that analysts and mutual fund managers affiliated with such “inside brokers” have a substantial information advantage on the insider’s firm. Affiliated analysts issue more accurate earnings forecasts, and affiliated mutual funds trade the insider’s stock more profitably than their peers, following insider trades through their brokerage. Notably, this advantage persists well after these insider trades are publicly disclosed. Our results challenge the prevalent perception that information asymmetry arising from insider trading is acute only before trade disclosure, and suggest that brokers facilitating these trades are in a position to exploit this asymmetry.